The functional roles of marine sponges - Bell, James J. (Estuarine, coastal and shelf science, 2008)
Despite the wide range of functional roles performed by marine sponges they are still poorly represented in many research, monitoring and conservation programmes. The aim of this review is to examine recent developments in our understanding of sponge functional roles in tropical, temperate and polar ecosystems. Functions have been categorised into three areas: (a) impacts on substrate (including bioerosion, reef creation, and substrate stabilisation, consolidation and regeneration); (b) bentho-pelagic coupling (including carbon cycling, silicon cycling, oxygen depletion and nitrogen cycling); and (c) associations with other organisms (facilitating primary production, secondary production, provision of microhabitat, enhanced predation protection, survival success, range expansions and camouflage though association with sponges, sponges as a settlement substrate, disrupting near-boundary and reef level flow regimes, sponges as agents of biological disturbance, sponges as releasers of chemicals and sponges as tools for other organisms). The importance of sponges on substrate, sponge bentho-pelagic coupling, and sponge interactions and associations is described. Although the scientific evidence strongly supports the significance and widespread nature of these functional roles sponges still remain underappreciated in marine systems.